C++ programming with COBRA - 4 0 16; Vogel, Andreas; 5 (New York:;New York : John Wiley & Sons,;John Wiley, 1999)
Never before have C++ programmers been able to implement fully portable C++/CORBA code. Now, learn how to write code independent of a specific C++ ORB using only CORBA compliant features, including the Portable Object Adapter. You'll quickly master the skills you need to create powerful, C++-based business applications that interact with objects located anywhere on a network or the Internet, regardless of differences in operating systems or languages. This guide provides an introduction to CORBA, the C++ mapping, and the C++ mapping for the Portable Object Adapter (POA)
Ch. 1. Introduction -- Ch. 2. CORBA Overview -- Ch. 3. OMG IDL to C++ Mapping -- Ch. 4. ORB Runtime System -- Ch. 5. Discovering Services -- Ch. 6. Building Applications -- Ch. 7. Advanced Features
Includes index.
Keywords: 2 -- 0; 6; CORBA (Computer architecture).;C++ (Computer program language).; 20; 2